EVALUATION OF INTEGRATED NITROGEN AND PHOSPHOROUS MANAGEMENT USING THE TT BIPLOT METHOD IN SOYBEAN - shiri janagard, manochehr; kamrani, morteza; Ebadi, asghar (Journal of Agricultural Sciences (Belgrade), 2020)
To investigate the effects of integrated nutrients management on oil, protein seed yield and some traits of soybean (Glycine max L.), we conducted a factorial experiment with control based on randomized complete block design with four replications at the research farm of the University of Mohaghegh Ardabili, Iran. Analyses of variance indicated that most of the traits measured were (P>0.01) affected definitely by the treatment combinations. For better analysis of treatment combination × trait interaction, the biplot analysis as treatment × trait (TT) biplot used to find which treatment combination was best and for what trait. The two first biplots axes explained 94 and 96% of the total variation of the standardized data in 2017 and 2018, respectively. Accordingly, application of Biosoy and 150 Kg.ha-1 urea + 200 Kg.ha-1 diammonium phosphate significantly increased plant height at harvest, number of grains per plant, biomass, hundred grain weight, oil and protein yield, protein percent and grain yield compared to the other treatment combinations. The results showed that there are positive correlations between these traits. Also, non-inoculated and non-use of chemical fertilizers significantly increased oil percent. The results indicated that higher yielding treatment combinations are the poorest in oil percent. The biplot was used for ranking of treatment combinations based on a single trait. This investigation results suggested that bio-fertilizers has favorable effect on soybean and it can reduce the use of chemical fertilizers. The study revealed that TT biplot can graphically display the interrelationships between traits and help visual comparison of treatments.